Stab Incision Glaucoma Surgery: A Modified Guarded Filtration Procedure for Primary Open Angle Glaucoma - Soosan Jacob; Michele Figus; Dhivya Ashok Kumar; Ashvin Agarwal; Amar Agarwal; Saijimol Areeckal Incy (Journal of Ophthalmology)
Purpose. To describe a modified guarded filtration surgery, stab incision glaucoma surgery (SIGS), for primary open angle glaucoma (POAG). Methods. This prospective, interventional case series included patients with POAG (IOP ≥21 mmHg with glaucomatous visual field defects). After sliding superior conjunctiva down over limbus, 2.8 mm bevel-up keratome was used to create conjunctival entry and superficial corneoscleral tunnel in a single step starting 1.5 mm behind limbus. Lamellar corneoscleral tunnel was carefully dissected 0.5–1 mm into cornea and anterior chamber (AC) was entered. Kelly Descemet’s punch (1 mm) was slid along the tunnel into AC to punch internal lip of the tunnel, thereby compromising it. Patency of ostium was assessed by injecting fluid in AC and visualizing leakage from tunnel. Conjunctival incision alone was sutured. Results. Mean preoperative IOP was 27.41±5.54 mmHg and mean postoperative IOP was 16.47±4.81 mmHg (n=17). Mean reduction in IOP was 38.81±16.55%. There was significant reduction of IOP (p<0.000). 64.7% had IOP at final follow-up of <18 mmHg without medication and 82.35% had IOP <18 mmHg with ≤2 medications. No sight threatening complications were encountered. Conclusion. Satisfactory IOP control was noted after SIGS in interim follow-up (14.18±1.88 months).